PERBANDINGAN PENGARUH LATIHAN BENCHPRESS DAN LATIHAN UPRIGHTROW TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA ATLIT VOLI PUTRA PENDIDIKAN OLAHRAGA UNIVERSITAS RIAU - Saputra, Agung Saputra Agung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study, that the strength of the arm and shoulder muscles in men's volleyball athletes Physical Education University of Riau less than the maximum. The purpose of this study is to see Comparison Differences and the Effects of Exercise Bench Press Upright Row Strength Against Arm and Shoulder Muscles In Men's Volleyball Athlete of Physical Education University of Riau.This research is a quasi- experiment to see the effects of this form of exercise. The population in this study were all athletes son of Physical Education University of Riau, amounting to 20 people. The sampling technique is the total sampling, which means that the entire population sampled is then sampled in this study amounted to 20 people. Instrument in this study using Expanding Dynamometer tests to see Arm and Shoulder Muscle Strength.Analyses were performed using t-test.The research concludes that there is an influence on the Bench Press exercise on muscle strength in the arms and shoulders men's volleyball athletes Physical Education University of Riau proven to thitung 5393 > 2262 ttable at α = 0.05. There Upright Row exercise effect on muscle strength in the arms and shoulders men's volleyball athletes Physical Education University of Riau proved with 6,806 t count > t table 2262 at α = 0.05. There is a significant difference betweenexercise Bench Press and Upright Row against the arm and shoulder muscle strength in men's volleyball athletes Riau University of Physical Education where 2,302 t count > t table 2.101 at α = 0.05. Where the effect of exercise Bench Press is better when compared to the Upright Row exercise the arm and shoulder muscle strength in men's volleyball athletes Sports Education University of Riau. Keywords: ExerciseBenchPressandUprightRow, Strength Of Arm and Shoulder Muscles.